A cross-sectional observational study of high override rates of drug allergy alerts in inpatient and outpatient settings, and opportunities for improvement. Issue 3 (18th March 2016) - Slight, Sarah Patricia; Beeler, Patrick E; Seger, Diane L; Amato, Mary G; Her, Qoua L; Swerdloff, Michael; Dalleur, Olivia; Nanji, Karen C; Cho, InSook; Maniam, Nivethietha; Eguale, Tewodros; Fiskio, Julie M; et al.
Abstract : Objectives: To evaluate how often and why providers overrode drug allergy alerts in both the inpatient and outpatient settings. Design: A cross-sectional observational study of drug allergy alerts generated over a 3-year period between 1 January 2009 and 31 December 2011. Setting: A 793-bed tertiary care teaching affiliate of Harvard Medical School and 36 primary care practices. Participants: Drug allergy alerts were displayed for a total of 29 420 patients across both settings. Main outcome measures: Proportion of drug allergy alerts displayed and overridden, proportion of appropriate overrides, proportion of overrides in each medication class, different reasons for overriding and types of reactions overridden. Results: A total of 158 023 drug allergy alerts were displayed, 131 615 (83%) in the inpatient setting and 26 408 (17%) in the outpatient setting; 128 157 (81%) of which were overridden. A random sample of inpatient (n=200, 0.19%) and outpatient (n=50, 0.25%) alert overrides were screened for appropriateness, with >96% considered appropriate. Alerts for some drug classes, such as 'non-antibiotic sulfonamides', were overridden for >81% of prescriptions in both settings. The most common override reason was patient has taken previously without allergic reaction . In the inpatient setting alone, 70.9% of alerts that warned against the risk of anaphylaxis were overridden. Conclusions: The information contained in patients' drug allergy lists needs to be regularly updated. Most of the drug allergy alerts were overridden, with the majority of alert overrides in the subsample considered appropriate. Some of the rules for these alerts should be carefully reviewed and modified, or removed. Further research is needed to understand providers' overriding of alerts that warned against the risk of 'anaphylaxis', which are more concerning with respect to patient safety.